SIMULACRA IN INDONESIAN TOURISM: A STUDY OF THE THEME PARK PHENOMENON OF JATIM PARK 3 in Batu City, East Java - Amma Ghifar Ibrahim (Journal of Development and Social Change, 2026)
This study discusses the dinosaur simulacra found in the Jatim Park 3 theme park. Simulacra in theme parks are used by corporations to attract visitors’ interest with the aim of capital accumulation. The research also explores how media narratives are utilized by corporations and how visitors engage in the consumption of signs related to the simulacra within the theme park. This is aqualitative study using a phenomenological approach, focusing on the phenomenon of simulacra present in Jatim Park 3. The data collection technique employed in this research is non-probability sampling with a purposive sampling approach. The criteria for informants in this study are as follows: they must be visitors of Jatim Park 3, have direct experience in the Dino Park attraction, and possess relevant knowledge related to the research subject. This study uses source triangulation to ensure data validity. The data analysis technique involves data collection, data reduction, data presentation, and conclusion drawing. The results of the study show that Jatim Park 3 is filled with simulacra. These simulacra are presented through media narratives rich in hyperreality, which are used by corporations to attract visitors. Moreover, visitors engage in the consumption of simulacra signs in various ways, such as taking photos, interacting with, and playing with the simulacra present in the theme park.The simulacra in Jatim Park 3 are constructed by corporations through media narratives, and visitors consume these hyperreal signs, partly due to exposure to such narratives. Thus, simulacra are not only found within the physical attractions of the theme park but also exist externally through the media narratives conveyed.Keywords: theme park, media narrative, simulacra, hyperreality sign consumption